2018
DOI: 10.1177/0023830917749275
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Phonological Mid Vowel Intuitions in Central Catalan

Abstract: Catalan, like other Romance languages, has two pairs of phonemic mid vowels (/be/ "well" vs. /bɛ/ "lamb"; /os/ "bear" vs. /ɔs/ "bone"). However, these contrasts do not function like others in the language: they are partially phonologically conditioned, and evidence shows that words may be pronounced with different mid vowels by speakers of the same variety or even by the same speaker. Spanish may influence this instability, as first-language Spanish Catalan-Spanish bilinguals struggle to perceive and produce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…In a production-based task, Nadeu and Renwick (2016) compared the acoustics of mid vowels against native speakers' own intuitions of height and found that intuitions do not uniformly correspond to productions; speakers with poor intuitions may exhibit increased acoustic overlap between higher and lower mid vowels. Linking marginal contrast with bilingualism and language change, a large-scale Internet survey showed that speakers with higher Catalan dominance have increased confidence in making and judging height distinctions and that older speakers are more likely to use low /E O/ (Renwick and Nadeu 2018). The survey confirmed a synchronic link between phonological context and mid vowel height: judgments were more confident and consistent in segmental contexts where low mid vowels were historically preferred (Renwick and Nadeu 2018;cf.…”
Section: Marginal Contrasts In Romance Languagesmentioning
confidence: 85%
“…In a production-based task, Nadeu and Renwick (2016) compared the acoustics of mid vowels against native speakers' own intuitions of height and found that intuitions do not uniformly correspond to productions; speakers with poor intuitions may exhibit increased acoustic overlap between higher and lower mid vowels. Linking marginal contrast with bilingualism and language change, a large-scale Internet survey showed that speakers with higher Catalan dominance have increased confidence in making and judging height distinctions and that older speakers are more likely to use low /E O/ (Renwick and Nadeu 2018). The survey confirmed a synchronic link between phonological context and mid vowel height: judgments were more confident and consistent in segmental contexts where low mid vowels were historically preferred (Renwick and Nadeu 2018;cf.…”
Section: Marginal Contrasts In Romance Languagesmentioning
confidence: 85%
“…The recommended students and one of their parents received a small compensation gift after completing the online student and parental questionnaires, in either Cantonese or English versions, via “google form.” The student questionnaires were designed based on the Bilingual Language Profile (BLP, Birdsong et al, 2012 ), a widely used tool for assessing speakers’ bilingualism (e.g., Amengual, 2016 ; Renwick and Nadeu, 2019 ; Aldrich, 2020 ). The degree of bilingualism was examined along four modules separately for L1 and L2, including “language history,” “language use,” “language proficiency,” and “language attitudes.” Similarly, the parental questionnaires also consisted of four modules, including “language history for parents,” “language education history for children,” “language proficiency for parents,” and “Urdu proficiency for children.” Also, their Chinese teachers were invited to assess their students’ proficiency in Cantonese.…”
Section: Methodsmentioning
confidence: 99%
“…The recommended students and one of their parents received a small compensation gift after completing the online student and parental questionnaires, in either Cantonese or English versions, via "google form. " The student questionnaires were designed based on the Bilingual Language Profile (BLP, Birdsong et al, 2012), a widely used tool for assessing speakers' bilingualism (e.g., Amengual, 2016;Renwick and Nadeu, 2019;10.3389/fpsyg.2022.918737 Frontiers in Psychology 06 frontiersin.org Aldrich, 2020). The degree of bilingualism was examined along four modules separately for L1 and L2, including "language history, " "language use, " "language proficiency, " and "language attitudes. "…”
Section: Participantsmentioning
confidence: 99%
“…/e-ɛ/ and /o-ɔ/ (Regueira, 1996), while Spanish only distinguishes a single mid front and mid back vowel. Previous work from Galician and other Romance languages, has shown that these contrasts are particularly difficult to acquire and maintain (Amengual, 2016;Amengual & Chamorro, 2015;Mora, Keidel & Flege, 2015;Mora & Nadeu, 2012;Nadeu & Renwick, 2016;Pallier, Bosch & Sebastián-Gallés, 1997;Renwick & Ladd, 2016;Renwick & Nadeu, 2018;Tomé Lourido & Evans, 2015Simonet, 2011). This instability has not only been documented in bilingual settings where acquisition and maintenance may be adversely affected by interaction with a language that lacks mid vowel contrasts, as in the case of Galician and Catalan, but also in monolingual settings.…”
Section: Mid Vowel Contrasts and The Galician Contextmentioning
confidence: 99%